PENGARUH VARIASI UMUR BETON TERHADAP CEPAT RAMBAT GELOMBANG DENGAN MENGGUNAKAN METODE NON DESTRUCTIVE TEST - Alif Iqbal Nur Hidayat; Indra Waluyohadi; Sugeng Prayitno Budio (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2019)
Field testing is divided into 2 tests i.e. by destroying test structures or destructive tests and without destroying the structure or called a non-destructive test (NDT) One of them using the ultrasonic pulse rate (UPV). The study used the PUNDIT PL-200 tool to perform a concrete density analysis process based on the parameters generated from the UPV tool. The parameters taken on this test are rapid ultrasonic wave velocity. The study used a cylinder test object with a diameter of 15 cm and a height of 30 cm. test objects are differentiated into 4 age of concrete 7 days, 14 days, 21 days, and 28 days. The results that get in the study's quick value of wave vines are constantly increasing according to the age